RETROSPECTIVE ANALYSIS OF INTRACRANIAL AND INTRASPINAL SPACE OCCUPYING LESIONS AT A TERTIARY CARE CENTER- A FIVE YEAR STUDY - Patil, Meena B.; Karandikar, Manjiri N. (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Tumors of Central Nervous System constitute approximately 2% of all malignancies. Cancers of the central nervous system (CNS) are considered to be among the most notorious of all cancers. Low-grade cns tumors have been found over time to progress to high grade tumors. CNS is a common site for metastasis from other organs. Due to newer techniques used in radio diagnosis and stereotactic biopsies, more & more CNS tumors are being diagnosed & are being operated upon. Aims and objectives: The objective of this article is to provide an overview of intracranial and intraspinal space occupying lesions at a single tertiary care referral center. The aim was to study incidence of various lesions in light of the WHO classification of tumours of the central nervous system, 2016 and to study relevant statistics. Material and methods: A total of 124 cases were received between January,2007 & December, 2011 at Bharati Vidyapeeth Deemed University Medical College and Hospital, Pune. Intraoperative diagnosis was desired in 70 cases. The final diagnoses in all the cases were made on Hematoxylin and Eosin stained slides of routinely processed tissue. Results: Neoplastic lesions comprised 83.88 %, including metastatic tumors while 16.12 % were nonneoplastic. A wide range of histopathological spectrum of CNS tumors was observed and was classified according to WHO classification of CNS tumors, 2016. The primary CNS tumors were graded from Grade I to IV according to WHO grading system, 2016. Astrocytic tumors constituted the largest category with 33 cases and most of the astrocytomas were grade II at the time of diagnosis. Incidence was more in females than males and maximum number of lesions were seen in fifth and sixth decades of life. Conclusion: This study highlights the histological diversity of CNS tumors in both adults and children. The most common destructive but nonneoplastic lesions like, infections/abscesses, infarct and cysts can be diagnosed, by crush cytology and frozen section for the definitive management.